Hospital competition with soft budgets - Brekke, Kurt R. (2012)
We study the incentives for hospitals to provide quality and expend cost-reducing effort when their budgets are soft, i.e., the payer may cover deficits or confiscate surpluses. The basic set up is a Hotelling model with two hospitals that differ in location and face demand uncertainty, where the hospitals run deficits (surpluses) in the high (low) demand state. Softer budgets reduce cost efficiency, while the effect on quality is ambiguous. For given cost efficiency, softer budgets increase quality since parts of the expenditures may be covered by the payer. However, softer budgets reduce cost-reducing effort and the profit margin, which in turn weakens quality incentives. We also find that profit confiscation reduces quality and cost-reducing effort. First best is achieved by a strict no-bailout and no-profit-confiscation policy when the regulated price is optimally set. However, for suboptimal prices a more lenient bailout policy can be welfare improving.